Students’ Self-Confidence in Their English-Speaking Fluency: A Case Study at SMP Islam Terpadu Generasi Muslim Cendikia - Baktillah, Annisa Faiza; Amrullah, Amrullah; Putera, Lalu Jaswadi; Muhaimi, Lalu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research aims to determine how students' self-confidence is seen from their fluency in speaking English, types of self-confidence in students seen from their self-confidence, and also the strategies used by teachers to increase students' self-confidence at SMP Islam Terpadu Generasi Muslim Cendikia. This research uses a qualitative descriptive method. Data were collected using observation techniques, speaking tests, questionnaires, and interviews. The subjects were 24 female students of class VIII/C at SMP Islam Terpadu Generasi Muslim Cendikia. The observations were indirect observations, where the researcher was not directly involved in the activities. A speaking rubric was used to measure the level of fluency in speaking English, and student self-confidence was determined based on self-confidence indicators during student speaking. For the questionnaire, a Likert scale is used and finally, the researcher conducted interviews were conduct is used with related teachers to determine strategies to increase student self-confidence. Based on the results of the analysis the results of the speaking test and survey questionnaire showed that students who have a high level of confidence also have high scores, and vice versa. There are 5 kinds of self-confidence in students, namely confidence in speaking in formal situations, confidence in speaking in class discussions, confidence in speaking with peers, confidence in speaking in everyday situations, and confidence in speaking in academic contexts, it is also found that there are 8 strategies that teachers can use to increase students' self-confidence.